(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Chrysin is a very effective naturally occurring polyphenol belonging to the subclass of flavones showing abundant biological activities, including potential antioxidant and anticancer activity in numerous cancerous cells. In the present study, the properties of Chrysin were evaluated by performing the analytical method development using UV spectrophotometry and comparing its validation parameters in methanol (λmax-219 nm), distilled water (λmax-267 nm), 1.2pH buffer (λmax-269.6 nm) and 6.8pH buffer (λmax-268.2 nm). It was analyzed by high performance liquid chromatography (HPLC), high performance thin layer chromatography (HPTLC) and fourier transform infrared spectroscopy (FT-IR) studies. The characterization of Chrysin was performed using differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X ray diffraction (XRD) studies and its log P value was evaluated. The in vitro antioxidant activity of Chrysin was evaluated using Ferrous ion chelation assay. The anticancer effect of Chrysin was studied on henrietta lacks immortal cell line (HeLa) by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) tetrazolium assay. The analytical method development and validation parameters confirmed the linearity, method reliability, accuracy, precision, and stability of Chrysin with RSD values < 2%. The HPLC analysis showed a sharp symmetric peak for Chrysin at a retention time of 3.036 min in the mobile phase, acetonitrile: methanol (65:35 v/v). The HPTLC analysis indicated the Rf value of 0.50 and 0.53 at 254 and 366 nm respectively for 5 μL sample in the mobile phase toluene: n-hexane: isopropyl alcohol (7:2:1 v/v). The FTIR and DSC studies confirmed the functionality and thermal behavior of Chrysin. The log P value of 3.236 indicated the high lipophilicity of Chrysin. SEM and XRD study suggested its crystalline behavior. The in-vitro Ferrous metal ion chelation was found in the range from 96.23 to 88.23% for concentrations ranging from 20–200 μg/mL. This indicated the increase in antioxidant activity of Chrysin with increase in its concentration. The MTT assay depicted the increasing concentration of Chrysin on HeLa cells and confirmed its anticancer effect by inhibiting the cell growth at IC50 value of 15 μM.